Behavior of tellurium during vacuum thermal decomposition of Ag–Cu–Te alloy - Jia Deng; Hongjun Ding; Huan Luo; Xianjun Lei; Baoqiang Xu; Bin Yang (Journal of Materials Research and Technology)
Ag–Cu–Te alloy is inevitable to be produced in the process from lead-copper anode slime to extract precious metals. It has been prone to the situation where tellurium would deposit on the cathode and affect the quality of silver powders. Currently, the main processes of separating tellurium from Ag–Cu–Te alloy are through oxidation slagging or increasing the current density and pole spacing in the electrolysis, but these processes are long durations and high costs. This paper presents a green and efficient strategy for separating tellurium from Ag–Cu–Te alloy by vacuum thermal decomposition. The microscopic interactive mechanism between Ag, Cu, Te was explained by molecular dynamics calculations. The results demonstrate that the stability of Ag2Te structure is higher than that of Cu2Te structure, and tellurium in Cu2Te is easier to separate. The experimental results show the volatilization of tellurium reached 99.93% at 1523 K, 10 Pa, and 480 min holding time, and the content of tellurium in the residue was only 0.0045 wt%. This method will effectively remove tellurium from Ag–Cu–Te alloy and provide some ideas for the separation and recovery of precious metals.